The Influence Branding of Social Media to Improve Digital Business in Training and Consulting on Instagram - Kurniaji, Ridwan; Azizah, Nur; Yusup, Muhamad (Pandawan Sejahtera Indonesia, 2024)
In the post-pandemic era, Indonesian entrepreneurs are competing fiercely to promote and sell their products, aiming to boost economic growth and busi- ness resilience. HSP Academy, a company specializing in occupational safety and health training and consulting, is leveraging this momentum by adopting social media-based marketing to reach wider audiences. Recognizing Insta- gram’s power as an accessible and popular platform, HSP Academy utilizes it to share information about its certified training programs, accredited by the Ministry of Manpower of Indonesia and the National Professional Certifica- tion Agency (BNSP). Instagram’s mobile-friendly interface allows prospective clients to easily access information on certified courses, which supports HSP Academy’s visibility and accessibility in the digital space. This article examines effective strategies for advancing business on social media, specifically focus- ing on Instagram as a key promotional tool. By analyzing the digital marketing techniques that resonate on this platform, the author explores methods for op- timizing engagement with potential clients. Topics include content strategies, engagement tactics, and promotional techniques tailored to the digital market- place. Through a focus on best practices for social media marketing, especially within a business like HSP Academy, this discussion aims to offer insights into enhancing business visibility and reach in today’s digital-driven market